2009
DOI: 10.1007/s00404-009-1255-1
|View full text |Cite
|
Sign up to set email alerts
|

Term and preterm (<34 and <37 weeks gestation) placental pathologies associated with fetal growth restriction

Abstract: Placentas of preterm FGR neonates (either <37 weeks or <34 weeks gestation) reveal numerous pathologies reflecting uteroplacental insufficiency and abnormal blood supply. The presence of increased syncytial knots in preterm FGR neonates is probably due to exposure to hypoxia and reactive oxygen agents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
21
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 43 publications
(26 citation statements)
references
References 13 publications
3
21
0
Order By: Relevance
“…However, in IUGR placentas, SNAT2 staining intensity seemed to be lower in the syncytiotrophoblast. As expected, IUGR placentas presented (27), and it may reflect conditions of cellular distress (28). Hypoxia frequently affects IUGR babies, and it could increase the formation of syncytial knots (28) and decrease the expression of SNAT2 (19), as was found in our study population.…”
Section: Discussionsupporting
confidence: 83%
“…However, in IUGR placentas, SNAT2 staining intensity seemed to be lower in the syncytiotrophoblast. As expected, IUGR placentas presented (27), and it may reflect conditions of cellular distress (28). Hypoxia frequently affects IUGR babies, and it could increase the formation of syncytial knots (28) and decrease the expression of SNAT2 (19), as was found in our study population.…”
Section: Discussionsupporting
confidence: 83%
“…Our results are consistent with evidence suggesting different histologic features related to placental disease in early versus late gestations [43, 65, 184, 185]. The results of this study also support the view that angiogenic markers reflect pathways to preterm delivery that do and do not relate to preeclampsia [186].…”
Section: Commentsupporting
confidence: 91%
“…In keeping with the findings discussed above for PET, whilst placentas from FGR fetuses delivered at term have significantly increased frequencies of uteroplacental vascular lesions (especially infarcts) compared to normal controls, the incidence of such lesions is much lower than in preterm FGR, and many cases are histologically unremarkable [11,39,101]. Furthermore, it has been reported that compared to normal term pregnancies, placentas from FGR at term may have an increased incidence of other villous lesions including fibrosis, hypovascularity and avascularity, suggestive of fetal thrombotic events [102], although these changes had not been described in previous studies.…”
Section: Placental Pathology Of Fgr At Term (‘Late-onset' Fgr)mentioning
confidence: 69%